RU486 Mitigates Hippocampal Pathology Following Status Epilepticus - Wulsin, Aynara C.; Herman, James P.; Danzer, Steve C. (Frontiers in Neurology, 2016)
Status epilepticus induces rapid hyper-activation of the hypothalamo-pituitary-adrenocortical (HPA) axis. HPA axis hyperactivity results in excess exposure to high levels of circulating glucocorticoids, which are associated with neurotoxicity and depression-like behavior. These observations have led to the hypothesis that HPA axis dysfunction may exacerbate status epilepticus-induced brain injury. To test this hypothesis, we used the mouse pilocarpine model of epilepsy to determine whether use of the glucocorticoid receptor antagonist RU486 can attenuate hippocampal pathology following status epilepticus. Excess glucocorticoid secretion was evident one day after status epilepticus in the mice, preceding the development of spontaneous seizures (which can take weeks to develop). RU486 treatment blocked the SE-associated elevation of glucocorticoid levels in pilocarpine treated mice. RU486 treatment also mitigated the development of hippocampal pathologies induced by status epilepticus, reducing loss of hilar mossy cells and limiting pathological cell proliferation in the dentate hilus. Mossy cell loss and accumulation of ectopic hilar cells are positively correlated with epilepsy severity, suggesting that early treatment with glucocorticoid antagonists could have anti-epileptogenic effects.